The Influence of Principal Leadership, Rewards and Punishment from Principals on Teacher Discipline in Elementary Schools - Syuhada, Syuhada (Universitas Riau, 2022)
This research is a quantitative research with the Expost Facto method which aims to analyze and describe the influence of Principal Leadership, Rewards and Punishment from Principals on Teacher Discipline either partially or simultaneously. Data were collected using an instrument in the form of a closed questionnaire which was distributed to 93 respondents consisting of public elementary school teachers in the Dumai city after being tested for validity and reliability first. The results of the study show that partially Principal Leadership has a significant and positive effect on Teacher Discipline by 24.25% and it was the most dominant factor in influencing teacher discipline in this study. Reward from the Principal has a significant and positive effect on Teacher Discipline by 4.41%. Whilst, punishment from the Principal has a significant and positive effect on Teacher Discipline by 20.46%. Meanwhile, simultaneously the Principal's Leadership, Reward from Principal, and Punishment from Principal have a significant and positive effect on Teacher Discipline by 49.1%, while the remaining 50.9% is influenced by other variables outside of this study. This indicates that the principal’s leadership, reward and punishments from the principal do have an influence toward teacher discipline.